The Kribi Gas Power Project : Private, Local-Currency Financing Made Possible through an IDA Guarantee - Alvarez, Clara; Kacaniku, Teuta (World Bank, Washington, DC, 2015)
In the late 1990s the government of Cameroon initiated a reform to improve efficiency and increase private sector participation in the country s power sector. The reform included new legislation, a new regulator, and privatization of SONEL, the state-owned integrated power utility, which was transferred to private management under a 20-year concession in 2001. The concessionaire, Energy of Cameroon (ENEO), was granted exclusivity over transmission and distribution of electricity and the right to develop and own up to 1,000 MW of generating capacity. In the early 2000s the government of Cameroon decided to pursue the exploitation of offshore gas reserves for, among other things, incremental power generation. As a result, in March 2006, Perenco Cameroon, a subsidiary of French Perenco, signed a 25-year production-sharing agreement with Societe Nationale des Hydrocarbures (SNH), the state-owned gas supplier, to exploit the Sanaga South gas field. That agreement was the basis for the later development of the Kribi Gas Power Project.